An implementation science focused practice‐based research network for rural community pharmacies: RURAL‐CP - Delesha M. Carpenter; Stephanie Kiser; Megan Smith; Patricia Mashburn; Salisa C. Westrick; Tessa J. Hastings; Ashley Hannings; Meagen Rosenthal; Jure Baloh; Abigail Gamble; Tyler C. Melton; Geoffrey M. Curran (Wiley, 2024)
Abstract Practice‐based research networks (PBRNs) support the translation and evaluation of evidence‐based practices and interventions on a large scale and have primarily been used in primary care settings. Few pharmacy PBRNs exist. Our objective is to describe the composition and characteristics of the Rural Research Alliance of Community Pharmacies (RURAL‐CP), which is the first PBRN exclusively for rural community pharmacies. For each enrolled pharmacy, a pharmacist liaison completed a survey that assessed the pharmacy's operational characteristics, including business operations, human resource management, division of clinical responsibilities, technology and enhanced services, organizational context, and research priorities. Additionally, up to five other pharmacy staff members completed a brief survey on organizational context. Descriptive statistics were calculated. As of May 2023, there were 126 pharmacies across seven southeastern states that were enrolled in RURAL‐CP. Most pharmacies (91%) were independent pharmacies and operated 6 days per week (82%). On average, pharmacies employed 10 staff members and most trained student pharmacists. Pharmacies offered valuable services in their community, including immunizations, naloxone dispensing, and medication delivery. Blood glucose testing was the most common point‐of‐care (POC) test offered, and most pharmacies were interested in expanding POC offerings, particularly A1c testing and cholesterol screening. RURAL‐CP pharmacies have, on average, relatively strong organizational contexts and readiness for change. Pharmacists' top research priorities were expansion of clinical services, reimbursement, patient adherence, and addressing diabetes and hypertension. Although not generalizable to all rural pharmacies, results indicate that rural pharmacies deliver many important services in their communities and are interested in increasing services provided.